Solitude without Souls: Why Peter Unger hasn’t Established Substance Dualism - Bynoe, Will; Jones, Nicholas K. (Philosophia (Ramat Gan), 2013)
Unger has recently argued that if you are the only thinking and experiencing subject in your chair, then you are not a material object. This leads Unger to endorse a version of Substance Dualism according to which we are immaterial souls. This paper argues that this is an overreaction. We argue that the specifically Dualist elements of Unger’s view play no role in his response to the problem; only the view’s structure is required, and that is available to Unger’s opponents. We outline one such non-Dualist view, suggest how to resolve the dispute, respond to some objections, and argue that ours is but one of many views that survive Unger’s challenge. All these views are incompatible with microphysicalism. So Unger’s discussion does contain an insight: if you are the only conscious subject in your chair, then microphsyicalism is false. Unger’s mistake was to infer Substance Dualism from this; for microphysicalism is not the only alternative to Dualism.